Examination of co-construction of knowledge in videotaped simulated instruction - Kuter, Sıtkıye; Altinay, Zehra; Altinay, Fahriye (International Forum of Educational Technology and Society,National Taiwan Normal University, 2012)
The aim of this study was to examine the impact of a videotaped simulated instructional model on prospective language teachers' co-construction of knowledge with the help of their peers and their supervisor in microteaching sessions. Within the framework of action research, a three-phase collaborative coaching model (TCCM) was developed to encourage trainees' reflection and instructional awareness regarding teaching and learning processes in videotaped simulated instruction. The implementation of the strategies of qualitative data and method triangulation and collaborative data analysis procedures helped the cross-examination and verification of the data which increased the credibility and objectivity of the research. The analysis of multiple data indicated that the three-phase videotaped simulated instruction is a viable model for trainees' professional growth. Being involved in video-mediated collaborative teaching and dialogue provided trainees with invaluable opportunities for an in-depth analysis of instructional processes, which raised not only their reflective skills but also professional awareness and development. © International Forum of Educational Technology & Society.
Keywords: Action research; Collaboration; Construction of Knowledge; Microteaching; Videotaped instructional design